2008
DOI: 10.1073/pnas.0709772105
|View full text |Cite
|
Sign up to set email alerts
|

Niche adaptation and genome expansion in the chlorophyll d -producing cyanobacterium Acaryochloris marina

Abstract: Acaryochloris marina is a unique cyanobacterium that is able to produce chlorophyll d as its primary photosynthetic pigment and thus efficiently use far-red light for photosynthesis. Acaryochloris species have been isolated from marine environments in association with other oxygenic phototrophs, which may have driven the niche-filling introduction of chlorophyll d. To investigate these unique adaptations, we have sequenced the complete genome of A. marina. The DNA content of A. marina is composed of 8.3 millio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
184
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(195 citation statements)
references
References 57 publications
6
184
0
2
Order By: Relevance
“…Structural analysis revealed that photoactive Phe a forms a hydrogen bond with the C9-keto group and D1-130 residue, the latter of which is glutamic acid in many oxygenic photosynthetic organisms including spinach; however this residue is replaced by glutamine in Synechocystis and A. marina (30,31). Replacement of glutamine with glutamic acid in a Synechocystis mutant induced an up-shift of potential by 15 mV (32).…”
Section: Discussionmentioning
confidence: 99%
“…Structural analysis revealed that photoactive Phe a forms a hydrogen bond with the C9-keto group and D1-130 residue, the latter of which is glutamic acid in many oxygenic photosynthetic organisms including spinach; however this residue is replaced by glutamine in Synechocystis and A. marina (30,31). Replacement of glutamine with glutamic acid in a Synechocystis mutant induced an up-shift of potential by 15 mV (32).…”
Section: Discussionmentioning
confidence: 99%
“…and C. concentrica (Fan et al, 2012), the TEFAP approach amplified reads that form a phylogenetic clade with C domains from the marine cyanobacteria Moorea producens (Jones et al, 2011) and Acaryochloris marina (Swingley et al, 2008). Within Scopalina sp.…”
Section: Metagenomic Mining Of Condensation Domains Reveals An Unprecmentioning
confidence: 99%
“…Another unique cyanobacterium, Acaryochloris marina, grows in biofilms on the underside of didemnid ascidians, where it uses chlorophyll (Chl) d to sustain its photosynthesis using near-infrared radiation (NIR; Kü hl et al, 2005). The A. marina type strain MBIC11017, originally isolated from L. patella, was hereafter sequenced and revealed a genome of unusually large size (Swingley et al, 2008). The relative abundance of A. marina in these epizoic microbial communities remains unknown and besides a recent genomic survey focusing on Prochloron, and its secondary metabolism (Donia et al, 2011), no further efforts have been made in studying the microbial diversity in L. patella.…”
Section: Introductionmentioning
confidence: 99%